2015
DOI: 10.1177/1526602814564384
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Renal Chimney Grafts on Anatomical Suitability for Endovascular Repair in Ruptured Abdominal Aortic Aneurysm

Abstract: Introduction: Open repair of the aorta carries a high risk for morbidity and mortality especially in the elderly population and in patients unfit for major surgery. Endovascular aortic repair is safe, durable and effective when there is adequate proximal and distal sealing zone for the aortic stent graft. Fenestrated and branched stent grafts have made the repair possible for complex but elective cases that do not have an adequate sealing zone. Urgent complex cases and patients with midaortic occlusive disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…In an anatomic study of 206 patients with ruptured aneurysms, Dias et al reported 33 patients (24.0%) with short necks, of whom 25 (76.0%) were potential candidates for a chimney repair. 34 This compares well with the 70.0% suitability of "off-theshelf" fenestrated endografts reported in a study evaluating "nonruptured" juxtarenal aneurysms. 32 The argument that CHIMPS are a treatment option for patients with anatomy unsuitable for FEVAR, in particular in those with angulated necks, is not supported by specific analysis.…”
Section: Discussionsupporting
confidence: 80%
“…In an anatomic study of 206 patients with ruptured aneurysms, Dias et al reported 33 patients (24.0%) with short necks, of whom 25 (76.0%) were potential candidates for a chimney repair. 34 This compares well with the 70.0% suitability of "off-theshelf" fenestrated endografts reported in a study evaluating "nonruptured" juxtarenal aneurysms. 32 The argument that CHIMPS are a treatment option for patients with anatomy unsuitable for FEVAR, in particular in those with angulated necks, is not supported by specific analysis.…”
Section: Discussionsupporting
confidence: 80%
“…Usually, EVAR is the best treatment for patients with preoperative renal dysfunction because EVAR does not need block abdominal aorta, which can minimize the damage to renal function. 28 Moreover, Powell et al have suggested that advanced age, renal failure, and chronic obstructive pulmonary disease may increase the risk of ruptured mortality of AAA. 29,30 Hence, for some elderly patients, especially for patients with multiple underlying diseases, EVAR has become an alternative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Different EVAR strategies have varying anatomic criteria for treating RAAAs (Table 2). [6][7][8][9][10][11][12][13][14][15][16][17] Strategies such as chimney EVAR (ch-EVAR) have already demonstrated high rates of aneurysm exclusion and patency of visceral branches. 18 However, this procedure may take more time than conventional EVAR, which can hinder its applicability in unstable patients.…”
Section: Discussionmentioning
confidence: 99%